1986
DOI: 10.1073/pnas.83.12.4561
|View full text |Cite
|
Sign up to set email alerts
|

Go, a guanine nucleotide-binding protein: immunohistochemical localization in rat brain resembles distribution of second messenger systems.

Abstract: We have localized a guanine nucleotide-bind-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

10
87
2

Year Published

1987
1987
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(99 citation statements)
references
References 30 publications
10
87
2
Order By: Relevance
“…A recent paper by Hescheler et al 13 indicates that α o may play a pivotal role in regulating Ca 2+ channel function in neurons. Furthermore, the recently reported co-localization of α o immunoreactivity and phorbol ester binding in brain 14 suggests the possibility that physiological processes regulated by this G protein may be mediated by protein kinase C. …”
mentioning
confidence: 98%
“…A recent paper by Hescheler et al 13 indicates that α o may play a pivotal role in regulating Ca 2+ channel function in neurons. Furthermore, the recently reported co-localization of α o immunoreactivity and phorbol ester binding in brain 14 suggests the possibility that physiological processes regulated by this G protein may be mediated by protein kinase C. …”
mentioning
confidence: 98%
“…G o has a less ubiquitous expression pattern than G i or G s and is highly expressed in the central and peripheral nervous systems, where it was originally identified (16,17). G o is also expressed in the heart and in the endocrine system, including the pituitary gland and pancreatic islets (18,19).Insulin secretion can be modulated through cAMP-dependent and -independent pathways (1, 20). Activation of G s in pancreatic β cells enhances insulin release through an adenylyl cyclase/ cAMP-mediated mechanism.…”
mentioning
confidence: 99%
“…G o has a less ubiquitous expression pattern than G i or G s and is highly expressed in the central and peripheral nervous systems, where it was originally identified (16,17). G o is also expressed in the heart and in the endocrine system, including the pituitary gland and pancreatic islets (18,19).…”
mentioning
confidence: 99%
“…These data suggest that the pertussis toxin substrate Gi, Go or a Gi/Go-like Gprotein may be involved in the phosphoinositide response in some cell types. Indirect evidence from Snyder's laboratory showed that immunohistochemical localizations of Go and protein kinase C correspond in many areas of the brain suggesting a potential role for Go in the regulation of the phosphoinositide response [21]. Reconstitution experiments using purified Go or Gi will provide valuable information to the above observations.…”
mentioning
confidence: 99%